Self Embedding Watermarking pada Citra Digital - Leonardo Petra Refialy (Journal Information System Development (ISD), 2020)
Digital watermark is a sign embedded in the digital media, such as images, audio, or video. Digital watermarks typically used to identify ownership of the copyright  of digital media. Digital watermarks may be used to verify the authenticity or integrity of the carrier media. Self-embedding means insert a duplicate of a digital image, into itself. Self-embedding can be implemented as watermarking. This modification will provide the advantage that the introduction of area changes / media damage if it fails to verify the authenticity of the digital media. Duplicates of the digital image is made, by choosing 2 MSB, using selective Bitplane, then pasted on the LSB digital image itself. In this study produced a self-embedding application, which can detect changes in the digital image. The results show that the technique of self-embedding and selective bitplane can be used to verify authentication or integrity, and also the detection of the location of the damage on a 24-bit color digital image.